Cognitive Control in Suicide Ideators and Suicide Attempters - Brokke, Silje Støle; Landrø, Nils Inge; Haaland, Vegard Øksendal (Frontiers in Psychology, 2020)
There is a need to understand more of the risk factors involved in the process from suicide ideation to suicide attempt. Cognitive control processes may be important factors in assessing vulnerability to suicide. A version of the Stroop procedure, Delis–Kaplan Executive Function System (D-KEFS) Color–Word Interference Test (CWIT) and Behavior Rating Inventory of Executive Function (BRIEF-A) were used in this study to test attention control and cognitive shift, as well as to assess everyday executive function of 98 acute suicidal psychiatric patients. The Columbia Suicide History Form (CSHF) was used to identify a group of suicide ideators and suicide attempters. Results showed that suicide attempters scored lower on attention control than suicide ideators who had no history of attempted suicide. The self-report in the BRIEF-A inventory did not reflect any cognitive differences between suicide ideators and suicide attempters. A logistic regression analysis showed that a poorer attention control score was associated with the suicide attempt group, whereas a poorer cognitive shift score was associated with the suicide ideation group. The results found in this study suggest that suicide attempters may struggle with control of attention or inhibiting competing responses but not with cognitive flexibility.